The Effectiveness of Blended Learning in Improving Students’ Workplace Communication Skills: A Case Study on Olive Website Test Result - Tyas, Agnes Siwi Purwaning; Muam, Ahmad; Sari, Yohana Ika Harnita; Dewantara, Cisya (Lingua Cultura, 2020)
The research aimed to investigate the effectiveness of using blended-learning instruction in improving students’ communication skills at Sekolah Vokasi Universitas Gadjah Mada. They were required to take the Test of English for Vocational Students (TEVOCS) and it indicated that there was a gap between listening and speaking ability as presented in the test scores. To support the improvement of both skills, blended-learning instruction was designed and carried out in the forms of online listening activities via Online Listening for Individual Practice (OLIVE) website and offline meeting for speaking activities. The research used experimental research, which referred to the results of pre-test and post-test scores of the group. The participants of the research were 275 students from three departments of Sekolah Vokasi Universitas Gadjah Mada; Language, Arts, and Cultural Management department; Engineering department; as well as Economic and Business department academic year 2019/2020. The pre-test and post-test scores show improvement in students’ performance in both skills. The result of the t-test also shows that there is significant improvement after the application of blended-learning instruction.